Industrial espionage – A systematic literature review (SLR). Issue 98 (November 2020) - Hou, Tie; Wang, Victoria
Abstract: Industrial Espionage (IE) is an umbrella term covering a complicated range of activities performed to gain competitive advantages, resulting in a huge amount of financial loss annually. Currently, techniques generated by rapid developments of Internet of Things (IOTs) and Data Science are enabling a massive increase of both frequency and power of IE related activities in our increasingly challenging global commercial environment. Thus, an in-depth understanding of IE is necessary. In this paper, we report a comprehensive Systematic Literature Review (SLR) of current English literature on IE. Particularly, we systematically: i) identify key features of IE by analysing its current definitions, and coin our own working definition; ii) discuss the current state of research on IE from different academic disciplines; iii) highlight some key challenges in the current state of research on IE; and iv) identify some possible trends in its future development. Further, based on our findings, we call for more multi-disciplinary/multi-agency research on IE in order to construct a comprehensive framework to combat IE.